2008
DOI: 10.1530/eje-07-0876
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endocrine testing of Leydig cell function using extractive and recombinant human chorionic gonadotropin and different doses of recombinant human LH in normal men

Abstract: Background: The functional testing of endocrine testis uses extractive human chorionic gonadotropin (ehCG). Recombinant human hCG (rhCG), avoiding any contamination, should replace ehCG. Moreover, a functional evaluation with recombinant human LH (rhLH) would be closer to physiology than a pharmacological testing with hCG. Methods: The study was conducted in normal men. We first evaluated the dose-effect of ehCG on plasma testosterone and estradiol levels, before and after injection of either hCG or vehicle. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 42 publications
(58 reference statements)
0
20
0
Order By: Relevance
“…The interval of 7 days after rhCG for hormonal assessment was chosen after a pilot study of five individuals in which hormonal data was measured at 3, 5, 7 and 10 days after rhCG; in this subjects testosterone peak response was obtained after 7 days. A previous study in adult healthy men found similar testosterone peak after 250 mcg rhCG and uhCG 5000 UI [6]. In vitro fertilization studies analysing oocyte maturation did not find significant differences in pharmacokinetics between both compounds [5, 7].…”
Section: Discussionmentioning
confidence: 91%
“…The interval of 7 days after rhCG for hormonal assessment was chosen after a pilot study of five individuals in which hormonal data was measured at 3, 5, 7 and 10 days after rhCG; in this subjects testosterone peak response was obtained after 7 days. A previous study in adult healthy men found similar testosterone peak after 250 mcg rhCG and uhCG 5000 UI [6]. In vitro fertilization studies analysing oocyte maturation did not find significant differences in pharmacokinetics between both compounds [5, 7].…”
Section: Discussionmentioning
confidence: 91%
“…Previous in vitro [36] and in vivo [37][39] studies did not pick up differences between the effects of hCG and hLH, probably because they were based on gonadotropins not quantified in exact molar terms but in “units” calibrated against a third preparation, e.g. the standard International Standard WHO 80/522 [18], or using in vivo bioassay (rat seminal vesicle weight gain assay).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found similar peak responses with such doses; the testosterone peak responses were reached 72 h after injections, and the mean testosterone increase over the baseline was 2.27-and 2.25-fold with uhCG and rhCG, respectively. The use of recombinant LH (rLH) determined a peak response after 4 h from intravenous injection, but the increment was about 25% from baseline values, confirming that hCG is able to attain a higher and longer stimulation of LH/CG receptor than LH itself [De Martino et al, 2003;Cailleux-Bounacer et al, 2008].…”
Section: Hcg Test: New Perspectivesmentioning
confidence: 99%